Recycling of AlSi8Cu3 alloy chips via high pressure torsion - Abd El Aal, Mohamed Ibrahim; Yoo Yoon, Eun; Seop Kim, Hyoung (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2013)
In this paper, AlSi8Cu3 alloy chips were consolidated via HPT at an applied pressure 8GPa for 10 revolutions at room temperature. The microstructure and hardness of the HPT consolidated chips were investigated and compared with those of the HPT processed solid AlSi8Cu3 alloy samples and cold compacted chip samples. The HPT process successfully resulted in fully densified bulk samples with a higher microhardness due to the finer Al matrix grains and Si particles sizes with more grain boundaries with high angles and more homogeneous deformation than those in the HPT processed solid AlSi8Cu3 alloy samples due to the higher imposed total strain.